Strategies for Improving Literacy and Numeracy in Computer-Based National Assessment at Madrasah Ibtidaiyah - Rosyada, Dede; Bariyah, N. Oneng Nurul; Hapsari, Tri Asihati Ratna (Scientechno: Journal of Science and Technology, 2025)
This study aims to identify and analyze strategies for improving literacy and numeracy in response to the Computer-Based National Assessment (ANBK) at Madrasah Ibtidaiyah Pembangunan Universitas Indonesia, Jakarta. National assessment results show that students’ literacy and numeracy skills still require improvement to meet established standards. The research investigates strategies employed by madrasahs through intracurricular and extracurricular activities, along with the use of technological infrastructure to enhance students’ literacy and numeracy outcomes. A descriptive approach with qualitative data analysis was used, involving observation, interviews, and documentation. Findings reveal strategies such as integrating literacy into learning, applying problem-based learning, and utilizing technology in assessments. Extracurricular activities like school literacy movements and technology-based numeracy training also contribute to better performance in the Computer-Based National Assessment. The study concludes that strengthening literacy and numeracy-focused learning strategies can boost students’ competencies in understanding and applying academic concepts. Effective collaboration among teachers, students, and policymakers is crucial for optimizing literacy and numeracy improvement strategies, creating a Smart Madrasah with Smart Learning & Assessment and a Digital Ecosystem that fosters innovative, inclusive educational environments.